Influence of the type of packaging on textural properties of minimally processed yellow Peruvian roots - Fernandes, Lara Santana; Corrêa, Paulo Cesar; Junqueira, Mateus; Finger, Fernando Luiz; Cecon, Paulo Roberto (Revista Ceres, 2016)
The textural properties of minimally processed products indicate its quality, and the package is fundamental to maintain the conservation of these foods. The aim of this study was to evaluate texture alterations that occur during the storage period of minimally processed yellow Peruvian roots, using texture profile analysis (TPA) and relaxation, in function of four types of plastic packaging, combined to refrigeration. The roots were selected, sanitized, peeled and sliced. The processing continued with final sanitization, rinsing and immersion in ascorbic and citric acid solution. The slices were centrifuged and packed in expanded polystyrene trays covered with PVC film, and in high-density polyethylene bags (HDPE), polypropylene bags (PP) and multilayer polyolefin bags for vacuum, and stored at 5 ± 2 ºC and 90 ± 5% relative humidity during 12 days. For the TPA, the parameters of interest were hardness and adhesiveness, automatically calculated from the force curves (F) x time (s). For modeling the relaxation process, the generalized Maxwell model was used. The slices packed in PP and vacuum showed higher hardness and normalized force in the balance (0.7502 and 0.7580, respectively), indicating that they were more elastic, better preserving the quality during storage than slices packed in other packaging.